(untitled) (International journal of artificial intelligence, 2024)
In this article, on the example of our nation's honored writers Mirkarim Osim and Oybek, an attempt is made to reveal how the figure of the great poet Alisher Navoi and his intelligence, philanthropy, his friendship with monarch HusaynBoyqaro, as well as his childhood and youth are described in Uzbek prose.